2018
DOI: 10.1111/pan.13422
|View full text |Cite
|
Sign up to set email alerts
|

Infraorbital foramen location in the pediatric population: A guide for infraorbital nerve block

Abstract: The infraorbital foramen was located within 2 mm, on average, from the nasospinale-to-jugale midpoint regardless of age group. Therefore, the nasospinale-to-jugale midpoint may serve as useful means of identifying the location of the infraorbital foramen in the pediatric population and aid in optimizing infraorbital nerve block procedures. The information in this report is valuable in general, but may be particularly useful in developing countries where there is a lack of ultrasound training and availability f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…Also, 54.8% of the IOF were circular, and the mean diameter of the foramina was 3.71 ± 0.63 mm, which did not show any statistically significant difference in all age groups [ 16 ]. Ali et al [ 9 ], Ilayperuma et al [ 18 ], and Zdilla et al [ 19 ] reported the presence of IOF above the vertical axis of the second premolar. However, in a study conducted in a cohort of Cameroonian adults, the IOF was located at the line passing below the maxillary first molar [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, 54.8% of the IOF were circular, and the mean diameter of the foramina was 3.71 ± 0.63 mm, which did not show any statistically significant difference in all age groups [ 16 ]. Ali et al [ 9 ], Ilayperuma et al [ 18 ], and Zdilla et al [ 19 ] reported the presence of IOF above the vertical axis of the second premolar. However, in a study conducted in a cohort of Cameroonian adults, the IOF was located at the line passing below the maxillary first molar [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ] and Zdilla et al . [ 12 ] who reported a greater presence above the vertical axis of the second premolar (PM2).…”
Section: Discussionmentioning
confidence: 99%